Psychometric Adaptation of the Flourishing Scale in Organizations with High Reliability: Empirical Evidence from Mining Employees in Indonesia - Sekar Saffina Dzaluliyyah Ardianto; Olievia Prabandini Mulyana (Universitas PGRI Yogyakarta, 2026)
The mining industry represents a high-risk work environment standardized psychometric instruments for measuring flourishing among Indonesian mining workers are currently limited. This study aims to examine the construct validity and reliability of the Flourishing Scale, adapted from the PERMA model (Positive Emotions, Engagement, Relationships, Meaning, and Accomplishment), among mining employees in Indonesia. Quantitative data from 262 employees, obtained through purposive sampling, were analyzed using Confirmatory Factor Analysis (CFA) with the assistance of JASP software, while internal reliability was estimated using Cronbach’s Alpha coefficient. The results indicated that the measurement model provided a very good fit to the empirical data, with CFI = 0.992, TLI = 0.990, and RMSEA = 0.025. All items yielded significant factor loadings, supported by high internal consistency (α = 0.859). As the first psychometric adaptation for this specific population in Indonesia, this study offers a significant original contribution to occupational psychology. The findings provide a robust, evidence-based instrument for Occupational Health and Safety (OHS) programs to enhance psychological well-being, mitigate human-factor risks, and support operational sustainability. Keywords: confirmatory factor analysis, flourishing, mining employees, construct validity, psychological well-being